2022
DOI: 10.1186/s12989-022-00465-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall iron oxide nanoparticles cause significant toxicity by specifically inducing acute oxidative stress to multiple organs

Abstract: Background Iron oxide nanoparticles have been approved by food and drug administration for clinical application as magnetic resonance imaging (MRI) and are considered to be a biocompatible material. Large iron oxide nanoparticles are usually used as transversal (T2) contrast agents to exhibit dark contrast in MRI. In contrast, ultrasmall iron oxide nanoparticles (USPIONs) (several nanometers) showed remarkable advantage in longitudinal (T1)-weighted MRI due to the brighten effect. The study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 44 publications
2
47
0
Order By: Relevance
“…In addition, the low CH 3 /CH 2 ratio in cells exposed to silica-coated SPIONs suggests the possibility that silica-coated SPIONs cause lipid peroxidation of cell membranes. Similar results were shown by Wu et al [7] who showed that ultrasmall SPIONs catalyze the Fenton reaction to produce •OH and cause lipid peroxidation due to the release of Fe 2+ in human breast cancer cells. OA was able to reduce the effects of silica-coated SPIONs on cell membranes, which is consistent with the study by Magtanong et al [42] showing that OA reduces the sensitivity of plasma membrane lipids to lipid peroxidation and resulting ferroptosis.…”
Section: Spectral Phenotype Of Cellssupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the low CH 3 /CH 2 ratio in cells exposed to silica-coated SPIONs suggests the possibility that silica-coated SPIONs cause lipid peroxidation of cell membranes. Similar results were shown by Wu et al [7] who showed that ultrasmall SPIONs catalyze the Fenton reaction to produce •OH and cause lipid peroxidation due to the release of Fe 2+ in human breast cancer cells. OA was able to reduce the effects of silica-coated SPIONs on cell membranes, which is consistent with the study by Magtanong et al [42] showing that OA reduces the sensitivity of plasma membrane lipids to lipid peroxidation and resulting ferroptosis.…”
Section: Spectral Phenotype Of Cellssupporting
confidence: 87%
“…Due to their superparamagnetic properties, SPIONs have great potential for use in medicine as magnetic drug carriers, in the treatment with magnetic hyperthermia, as contrast agents in magnetic resonance imaging, and for imaging with superparamagnetic NPs [2][3][4]. SPIONs are generally considered safe and biocompatible, but recent studies suggest they might cause aberrant cellular responses, including DNA damage, oxidative stress, mitochondrial membrane dysfunction, changes in gene expression, and lipid peroxidation [5][6][7][8]. Therefore, a detailed understanding of SPION-cell interactions and identification of approaches to reduce the side effects caused by SPIONs could improve their applicability for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study different acellular assays along with a HEK293 cell-based NRF2 reporter assay were compared to study the generation of ROS and antioxidant responses of engineered nanomaterials. It is notable that the HEK293 cell-based NRF2 reporter assay did not show any concentration-dependent reactivity for the Fe-based nanomaterials ( Seleci et al, 2022 ), while Fe 3 O 4 nanomaterials have been shown to be able to induce oxidative stress in rodents ( Wu et al, 2022 ). The U2OS-NRF2 cells have a low number of receptors expressed, so that the potential for crosstalk between signal transduction pathways is very low.…”
Section: Discussionmentioning
confidence: 99%
“…However, cells are susceptible to programmed cell death when large amounts of iron accumulate, and small NPs are associated with greater cytotoxicity. 128 When the toxicity of iron ions is overcome, we believe that NPs such as lox-1-targeted iron oxide NPs will have bright prospects.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%